Asian Organization for Crohn's and Colitis and Asian Pacific Association of Gastroenterology consensus on tuberculosis infection in patients with inflammatory bowel disease receiving anti‐tumor necrosis factor treatment. Part 1: Risk assessment. Issue 1 (28th December 2017) - Park, Dong II; Hisamatsu, Tadakazu; Chen, Minhu; Ng, Siew Chien; Ooi, Choon Jin; Wei, Shu Chen; Banerjee, Rupa; Hilmi, Ida Normiha; Jeen, Yoon Tae; Han, Dong Soo; Kim, Hyo Jong; Ran, Zhihua; et al.
Abstract: Because anti‐tumor necrosis factor (anti‐TNF) therapy has become increasingly popular in many Asian countries, the risk of developing active tuberculosis (TB) among anti‐TNF users may raise serious health problems in this region. Thus, the Asian Organization for Crohn's and Colitis and the Asian Pacific Association of Gastroenterology have developed a set of consensus statements about risk assessment, detection, and prevention of latent TB infection and management of active TB infection in patients with inflammatory bowel disease (IBD) receiving anti‐TNF treatment. Twenty‐three consensus statements were initially drafted and then discussed by the committee members. The quality of evidence and the strength of recommendations were assessed by using the Grading of Recommendations Assessment, Development, and Evaluation methodology. Web‐based consensus voting was performed by 211 IBD specialists from nine Asian countries concerning each statement. A consensus statement was accepted if at least 75% of the participants agreed. Part 1 of the statements comprised two parts: (i) risk of TB infection during anti‐TNF therapy and (ii) screening for TB infection prior to commencing anti‐TNF therapy. These consensus statements will help clinicians optimize patient outcomes by reducing the morbidity and mortality related to TB infections in patients with IBD receiving anti‐TNF treatment.